Simple Mechanics to Upright Horizontally Impacted Molars with Ramus Screws - Lin, Shih-Yung; Chang, Chris; Roberts, W. Eugene (Orthodontic Journal of Nepal, 2016)
Simplified mechanics are reported for uprighting horizontally impacted mandibular molars with ramus bone screws. A 27-year-old male presented with a chief complaint of food impaction and problematic occlusion of his posterior teeth. The panoramic radiograph revealed multiple impacted molars: both upper third molars, and all lower second and third molars. Orthodontic treatment was indicated to improve occlusal function by aligning the posterior segments. The treatment plan was to extract the upper second molars and lower third molars, then upright the lower second molars, and allow the upper third molars to spontaneously erupt. The deeply impacted lower second molars were uprighted in only ~4 months with superiorly positioned ramus bone screws.